Development of An Assessment Instrument To Analyze Conceptual Abilities And Daily Life In PJOK Subject Questions Based On The Rasch Model - MUHAMMAD IZZUL AFRIZA; Hermawan Pamot Raharjo (Universitas Negeri Semarang, 2026)
This study aims to develop an assessment instrument to analyze conceptual understanding and application in everyday life (daily life) in Physical Education, Sports, and Health (PJOK) based on the Rasch Model. The research method used was Research and Development (R&D), adapting the development model from Gall, Gall, and Borg. The research procedure included a preliminary study, instrument design, expert validation, small-scale trials, large-scale trials, and dissemination of the final product. The developed instrument consisted of 16 essay questions that integrated conceptual mastery and application in everyday life contexts. Data were analyzed using content validity (Aiken's V), reliability (Cronbach's Alpha), and item characteristic analysis using the Rasch Model with the assistance of Winsteps software. The results showed that the instrument met the criteria for validity and reliability, and the items demonstrated a good level of fit. This instrument can be used by PJOK teachers as an evaluation tool capable of comprehensively describing students' minimum competencies.